Happiness Among the Elderly Living in Nursing Homes: A Qualitative Study - Anisa Silaturrahmi, Anisa Silaturrahmi; Yulia Nanda Safitri; Safuwan Safuwan; Nur Azzhahraini Azlia; Nabila Alea Kasta; Elfany Junaidi; Satria Rama Wijaya; Ridho Ahmad Octaviano (Jurnal Psikologi Terapan, 2025)
The phenomenon of happiness among the elderly living in nursing homes has attracted increasing scholarly attention due to its implications for psychological well-being and quality of life. This study explores the reconstruction of meaning and factors that contribute to elderly happiness within institutional settings in Indonesia. Through an integrative review of recent empirical studies from 2019 to 2025, the analysis identifies key determinants influencing happiness among residents of nursing homes, including religiosity, social support, psychological resilience, and engagement in daily activities. The findings reveal that spirituality and religious participation serve as essential coping mechanisms, fostering a sense of meaning and acceptance in later life. Social connectedness—manifested through peer relationships and staff support—also significantly enhances emotional satisfaction and reduces loneliness. Moreover, active involvement in structured social or religious programs contributes to a sense of belonging and purpose. Conversely, limited autonomy, weakened family ties, and inadequate emotional engagement were identified as major barriers to happiness. These insights align with the eudaimonic framework of well-being proposed by Ryff (1989) and the positive psychology perspective advanced by Seligman (2011), emphasizing that happiness in old age extends beyond pleasure to encompass meaning and self-realization. The study underscores the importance of a holistic care approach in Indonesian nursing homes—integrating psychosocial, spiritual, and cultural dimensions—to promote psychological well-being among the elderly.